Bilayer manganites: polarons in the midst of a metallic breakdown - Massee, F; Huang, S; Siu, W; Santoso, I; Mans, A; Boothroyd, A; Prabhakaran, D; Follath, R; Varykhalov, A; Patthey, L; Shi, M; Goedkoop, J; et al. (Nature Publishing Group, 2011)
The exact nature of the low temperature electronic phase of the manganite materials family, and hence the origin of their colossal magnetoresistant (CMR) effect, is still under heavy debate. By combining new photoemission and tunneling data, we show that in La{2-2x}Sr{1+2x}Mn2O7 the polaronic degrees of freedom win out across the CMR region of the phase diagram. This means that the generic ground state is that of a system in which strong electron-lattice interactions result in vanishing coherent quasi-particle spectral weight at the Fermi level for all locations in k-space. The incoherence of the charge carriers offers a unifying explanation for the anomalous charge-carrier dynamics seen in transport, optics and electron spectroscopic data. The stacking number N is the key factor for true metallic behavior, as an intergrowth-driven breakdown of the polaronic domination to give a metal possessing a traditional Fermi surface is seen in the bilayer system.